1982
DOI: 10.1002/ajpa.1330590408
|View full text |Cite
|
Sign up to set email alerts
|

Fatness and skeletal maturity of Belgian boys 12 through 17 years of age

Abstract: Relationships between fatness and skeletal maturity are considered in a nationwide sample of 14,259 Belgian boys 12 through 17 years of age (The Leuven Growth Study of Belgian Boys). Absolute fatness was estimated from four skinfolds using the Drinkwater and Ross technique and from the sum of four skinfolds, and was related to skeletal maturity assessed by the Tanner-Whitehouse method (I and II). In addition, comparisons were made between the fattest 5% and leanest 5% of the boys at each age level. Correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 14 publications
7
43
1
Order By: Relevance
“…Notwithstanding, excess fatness exerts a negative effect on those items of physical fitness in which the body is maintained in a bent arm position while hanging from a bar, moved or projected. In addition, fatness also has a negative effect on cardiorespiratory fitness (Beunen et al 1983). A significant negative relationship between aerobic fitness (walking treadmill protocol) and the rate of increasing adiposity was also observed by Johnson et al (2000) in North-American children, aged between 4.6 -11.0 years at baseline and followed annually for 3 -5 years.…”
Section: Tracking Of Body Fatness 63mentioning
confidence: 89%
“…Notwithstanding, excess fatness exerts a negative effect on those items of physical fitness in which the body is maintained in a bent arm position while hanging from a bar, moved or projected. In addition, fatness also has a negative effect on cardiorespiratory fitness (Beunen et al 1983). A significant negative relationship between aerobic fitness (walking treadmill protocol) and the rate of increasing adiposity was also observed by Johnson et al (2000) in North-American children, aged between 4.6 -11.0 years at baseline and followed annually for 3 -5 years.…”
Section: Tracking Of Body Fatness 63mentioning
confidence: 89%
“…The consequences of growth stunting and owt/ob for indicators of physical fitness in children and youth have been considered, respectively, in developing (Benefice, 1998;Fellmann et al, 1998;Henneberg et al, 1998;Prista, 1998;Monyeki et al, 2005) and developed (Beunen et al, 1983;Malina et al, 1995;Bovet et al, 2007;Malina, 2007, 2010) countries. This study is perhaps one of the first to compare the physical fitness of stunted, normal and owt/ob children living under marginal conditions in Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and obesity are a consequence of an imbalance between energy intake and expenditure. Obese children tend to have deficient movement skills (Graf et al, 2004;Okely et al, 2004) and physical fitness compared with normal weight children (Beunen et al, 1983;Malina et al, 1995;Malina, 2001;Bovet et al, 2007;Malina, 2007, 2010), whereas the evidence on physical activity in owt/ob youth is equivocal (Malina, 2001;Malina et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, information about the relationships between body composition and physical fitness in children from developed countries has been published (Malina, 1975(Malina, , 1994Beunen et al, 1983;Malina et al, 1995Malina et al, , 1998. These studies revealed that excessive fatness has a negative impact on performance tasks in which the body is projected through space, as in long jump, sprint, and on tasks in which the body must be lifted in space as in bent arm hang.…”
Section: Introductionmentioning
confidence: 99%